An Overview of the Catalytic Activity of mn4 Molecular Catalysts for the Heterogeneous Hydrogen Evolution Reaction - Zagal-Moya, J; Zagal-Moya, J; Venegas-Toledo, R (Elsevier B.V., 2023)
The electrocatalysis of the Hydrogen Evolution Reaction (HER) has been studied on metal electrodes and alloys for many years, mainly involving precious metals like Pt. The search for MN4-macrocyclic molecular HER catalysts is rather recent and pursues to reduce the dependence on expensive Pt-based catalysts. Some MN4 complexes are cost-effective and exhibit good activity, but many improvements are needed. Their activity can be modulated by changes in the molecular and electronic structure and can serve as models for this reaction. Many publications combine experiments and theory to quantify the influence of the N4 ligand and the central metal on the electrocatalytic properties of these materials. Their confinement on electrode surfaces is also described. In this review, we discuss the recent progress in this area and the factors that lead to high catalytic activity in terms of the molecular structure of catalysts and the influence of the nature of the support. © 2023 Elsevier B.V.